2006
DOI: 10.1093/jn/136.1.269s
|View full text |Cite
|
Sign up to set email alerts
|

Branched-Chain Amino Acids Activate Key Enzymes in Protein Synthesis after Physical Exercise

Abstract: BCAAs (leucine, isoleucine, and valine), particularly leucine, have anabolic effects on protein metabolism by increasing the rate of protein synthesis and decreasing the rate of protein degradation in resting human muscle. Also, during recovery from endurance exercise, BCAAs were found to have anabolic effects in human muscle. These effects are likely to be mediated through changes in signaling pathways controlling protein synthesis. This involves phosphorylation of the mammalian target of rapamycin (mTOR) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
198
1
13

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 306 publications
(225 citation statements)
references
References 39 publications
13
198
1
13
Order By: Relevance
“…REDD2 and its paralog REDD1 have been identified as negative regulators of mTOR (17), possibly through the control of the TSC1/2 complex (18). Thus a decrease in REDD2 mRNA expression is consistent with an activation of mTOR signaling following an anabolic stimulus (9,(21)(22)(23)30). The decrease in REDD2 mRNA during the recovery from this potent anabolic stimulus is in agreement with an increase in mTOR phosphorylation and elevated rates of protein synthesis in these same subjects (23).…”
Section: Discussionsupporting
confidence: 65%
“…REDD2 and its paralog REDD1 have been identified as negative regulators of mTOR (17), possibly through the control of the TSC1/2 complex (18). Thus a decrease in REDD2 mRNA expression is consistent with an activation of mTOR signaling following an anabolic stimulus (9,(21)(22)(23)30). The decrease in REDD2 mRNA during the recovery from this potent anabolic stimulus is in agreement with an increase in mTOR phosphorylation and elevated rates of protein synthesis in these same subjects (23).…”
Section: Discussionsupporting
confidence: 65%
“…The most important component responsible for the increased phosphorylation of p70 S6K with the whey protein ingestion is probably its large content of branched-chain amino acids that can elicit a similar p70 S6K response in the context of a bout of RE as observed in the present study (3,26). S6K1/p70 S6K has been shown in animal and cell models to be especially important in muscle hypertrophy (2,40,48).…”
Section: Discussionsupporting
confidence: 61%
“…Branched chain amino acids (BCAA, leucine, isoleucine, and valine) account for 35% of the essential amino acids found in muscle proteins (27,28). While the degradation of most amino acids occurs in the liver, BCAA are mostly metabolized in muscle tissue by mitochondrial dehydrogenase and branch-chain ketoacid dehydrogenase to produce the branch-chain keto acids (29).…”
Section: Amino Acids and Biogenic Aminesmentioning
confidence: 99%
“…While the degradation of most amino acids occurs in the liver, BCAA are mostly metabolized in muscle tissue by mitochondrial dehydrogenase and branch-chain ketoacid dehydrogenase to produce the branch-chain keto acids (29). The generated ketoacids are used by the muscle to generate ATP via the Kreb's cycle or transported to the liver for oxidation (27,28). Studies have suggested that muscle protein synthesis is upregulated by amino acids with leucine being the most potent (30,31).…”
Section: Amino Acids and Biogenic Aminesmentioning
confidence: 99%